1992
DOI: 10.4141/cjas92-002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding the beta-adrenergic agonist ractopamine on the behaviour of market-weight pigs

Abstract: . The effect of feeding the beta-adrenergic agonist ractopamine on the behaviour of market-weight pigs. Can. J. Anim. Sci. 72: [15][16][17][18][19][20][21]. A total of 86 ad libitum fed Lacombe bred barrows and gilts weighing on average 90 kg were used to determine the effect of feeding ractopamine on anirnal behaviour. Four treatment groups consisted of a control (N : 22) and three levels of ractopamine (10 ppm (N : 15), 15 ppm (N : 24) and 20 ppm (N --25) in the diet). The pigs received the ractopamine tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…They also tended to take longer to settle after disturbance. These results seem to counter the results of the only other study carried out on RAC-fed pigs (Schaefer et al, 1992), which noted only that pigs on RAC were less active. However, the different timing of behavioral observations between this study and the previous study means that these results are not necessarily in conflict.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…They also tended to take longer to settle after disturbance. These results seem to counter the results of the only other study carried out on RAC-fed pigs (Schaefer et al, 1992), which noted only that pigs on RAC were less active. However, the different timing of behavioral observations between this study and the previous study means that these results are not necessarily in conflict.…”
Section: Discussioncontrasting
confidence: 94%
“…These include increased gait problems and increased behavioral reactivity, especially in stressful situations. The behavioral research carried out so far has confirmed that after 6 wk of RAC, pigs spent more time lying and less time walking (Schaefer et al, 1992), but there was no evidence of decreased joint soundness (He et al, 1993), and there is no scientific evidence of behavioral or physiological responses to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Ractopamine has been evaluated for possible effects on animal welfare. As suggested by Schaefer et al (1992), the utilization of ractopamine in swine finishing diets did not cause marked changes in animal behavior even though pigs spent more time lying and less time walking during a 4-hour period. In contrast, MarchantForde et al (2003) observed that pigs fed 10 ppm ractopamine for four weeks were more active and had elevated heart rates and circulating catecholamine levels, making them more difficult to handle and potentially more susceptible to stress during handling and transport.…”
Section: Metabolic Responses Induced By Ractopaminementioning
confidence: 69%
“…In 1992, study using up to 15 ppm of ractopamine in pigs diets for up to six weeks from 64,0 kg, verified small effects of ractopamine on the stereotyped behavior and aggressive and these researchers inferred that the more time spent lying by animals than remained on ractopamine treatment wasn't responsible for marked changes in the behavior of pigs [41]. In 2010, one study using up to 10 ppm of ractopamine in diets for pigs from 90.0 to 107.0 kg in conditions of commercial production, observed improvements in performance and carcass quality and found no effects on the behaviour, number of skin lesions and carcass after transport [42].…”
Section: Ractopamine and Welfarementioning
confidence: 99%